Pengaruh Harga, Inovasi Produk Dan Citra Merek Terhadap Keputusan Pembelian Pada Distro Wildtime Kota Mataram - Fandi Maulana; I Made Murjana; Surahman Hidayat (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This study explores the influence of price, product innovation, and brand image on purchasing decisions in Wild Time Distro, Mataram. The results show that individually, price (0.248), product innovation (0.155), and brand image (0.386) have a positive and significant impact on purchasing decisions. Simultaneously, all three variables have a significant impact with a total magnitude of 108.505. Consequently, it is recommended that Wild Time enhances product innovation, strengthens brand image, and sets attractive prices to improve purchasing decisions. This study supports previous findings and suggests that future research consider additional variables such as product quality, location, promotion, and quality control in a broader context.